สิเน่หาแห่งเพศ : ชีวิตและความรักของผู้หญิงมุสลิมโสดในจังหวัดปัตตานี - จิตต์ปภัสสร์ บัตรประโคน (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This thesis focused on conditions affecting changes in personal space or intimate relationship in relation to love and expression of sexual passion of single muslim women in Pattani Province. The study results show that the social and cultural factors affecting love and intimate relationship, both those that are obstacles and those that allow for a choice of living a free life consist of religious, cultural, educational, economical, gender-related, and sexual factors. Negotiation with and reaction to these factors give definitions to love, sexual passion, and intimate relationship, about which each woman makes decisions with reason and self-awareness. There are many definitions to love, depending on the women’s personal experience. Love and experience in intersexual relationship of single Muslim women also reflect 2 major changes. The first one is love has reduced the importance of the concern of benefits and the second one is love leads to more opening, negotiation, and exploration of the partner’s feelings. The mode of relationship with partners is grounded in equality, exchange, and generation of emotional balance, accordance and suitability and what is especially important is the partners must be Muslims with faith. The women expect their partners to express their love through both actions and words. Love is the foundation of marriage and family. Women see that in premarital relationship it is important for partners to learn about each other within the frame of religion.